2010
DOI: 10.3727/096368910x514198
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Wharton's Jelly-Derived Stem Cells Alleviates Chemically Induced Liver Fibrosis in Rats

Abstract: There is currently no effective treatment method available for liver fibrosis. We therefore evaluated the use of Wharton's jelly stem cells (WJSCs; the major umbilical cord stem cell population) to treat chemically induced liver fibrosis via intraperitoneal injection of thioacetamide. WJSCs were transplanted into liverdamaged rats via the portal vein and the treatment was evaluated by assessing serum biochemistry and histopathology. Transplanted WJSCs were distributed in the fibrotic area and around blood vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 33 publications
(45 reference statements)
2
43
0
Order By: Relevance
“…Urea in the medium increased in a time-dependent manner both in FLCM and DMEM group. Seventy-two h and 96 h after NH 4 Cl addition, production of urea was significantly higher in the FLCM-treated cells compared with DMEM-cultured cells (Figure 2(c)). Furthermore, immunocytochemistry analysis showed that the number of cells expressing AFP, ALB, and CK-18 was increased in FLCMtreated hUCMSCs (Figure 2(d)).…”
Section: Hepatic Differentiation Of Flcm-induced Hucmscsmentioning
confidence: 91%
See 1 more Smart Citation
“…Urea in the medium increased in a time-dependent manner both in FLCM and DMEM group. Seventy-two h and 96 h after NH 4 Cl addition, production of urea was significantly higher in the FLCM-treated cells compared with DMEM-cultured cells (Figure 2(c)). Furthermore, immunocytochemistry analysis showed that the number of cells expressing AFP, ALB, and CK-18 was increased in FLCMtreated hUCMSCs (Figure 2(d)).…”
Section: Hepatic Differentiation Of Flcm-induced Hucmscsmentioning
confidence: 91%
“…The use of hUCMSCs have been applicated in the treatment of various hepatic injuries. [4][5][6] The clinical relevance of hUCMSCs is primarily dependent on their potential to differentiate. Like human bone marrow mesenchymal stem cells, hUCMSCs were demonstrated to be multipotent.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests faster engraftment and function of those cells that were injected intrahepatically (2). We previously reported that the transplantation of human BMMSCs and Wharton's jelly-derived stem cells through the portal vein can promote liver recovery after liver cirrhosis has occurred (5,17).…”
Section: Discussionmentioning
confidence: 99%
“…Various routes of ADSC administration for liver disease, including intravenous (IV) (3), hepatic portal vein (16,17,30), intrasplenic (8), and intrahepatic (10) have been reported for stem cell delivery. Of these routes, IV is a convenient strategy for cell delivery and has been shown to produce therapeutic effects to the delivery site.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other researchers have found that MSC are able to prevent liver fibrosis by suppressing the function of activated hepatic stellate cells, inducing their apoptotic death and diminishing collagen synthesis [155]. Studies like those by Lin et al have shown that MSC may utilize multiple mechanisms to exert their effects, both engrafting and differentiating into albumin-producing cells, and producing metalloproteinases that significantly reduced the collagen deposits in a rat model of chronic liver fibrosis [165]. However, these promising results must be interpreted carefully and with tempered enthusiasm, because other studies have suggested that under different conditions, transplanted MSC may actually contribute to the myofibroblast pool and thus enhance the fibrotic process within the liver [159,[166][167][168][169].…”
Section: Mesenchymal Stem Cells Differentiate In Vivo Into Hepatocytesmentioning
confidence: 99%